Synergistic effect of mesoporous metal oxides and PtO2 nanoparticles in aerobic oxidation of ethanol and ionic liquid induced acetaldehyde selectivity - Bingwa, Ndzondelelo; Ndolomingo, Matumuene Joe; Noh, Ji Hyang; Antonels, Nathan Charles; Carleschi, Emanuela; Doyle, Bryan P.; Haumann, Marco; Meijboom, Reinout (Molecular Catalysis, 2020)
We report on the catalytic performance of mesoporous metal oxides (MMOs) as catalysts and as potential supports for platinum (Pt) nanoparticles in aerobic oxidation of ethanol. Synthesis of MMOs was achieved through the hard-template method and the resulting MMOs resembled the 3-D structure of the templating KIT-6. The Pt nanoparticles were templated and stabilized using poly(amidoamide), PAMAM, dendrimer to achieve dendrimer-encapsulated Pt nanoparticles (Pt-DENs) with an average size of 3.5 ± 0.4 nm. All the components of the catalysts (Pt-DENs and MMOs) were first characterized separately and thereafter, followed the preparation of MMO-immobilized Pt nanoparticles. Upon characterization of the MMO-immobilized Pt nanoparticles, the Pt nanoparticle size increased as determined from hydrogen-chemisorption and organothiol-adsorption technique. Furthermore, X-ray photoelectron spectroscopy (XPS) revealed that Pt has an oxidation state of 4+ after removal of the dendrimer at 550 °C signifying an oxide state (PtO2). The hydrogen temperature-programmed reduction (H2-TPR) revealed a change in electronic structure of MMOs as reduction peaks shifted to lower temperatures upon immobilization of PtO2 nanoparticles. This change in electronic structure of the mesoporous metal oxides upon immobilization of PtO2 nanoparticles is found to be one of the reasons for enhanced catalytic activity. Improved selectivity towards acetaldehyde was induced by introduction of an ionic liquid layer in a solid catalyst with ionic liquid layer, SCILL concept. Furthermore, the amount of ionic liquid coating plays a pivotal role in impacting selectivity and has an impact in the reaction turnover frequency.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Adsorption; Ethanol oxidation; Ionic liquid; Mesoporous metal oxides; Platinum nanoparticles